Liminality in Women and Men After Love-bombing on Social Media - Safira, Nabila; Rosramadhana, Rosramadhana (QISTINA: Jurnal Multidisiplin Indonesia, 2024)
This study aims to uncover the phenomenon of love-bombing and how it triggers liminality in victims, as well as analyze the love-bombing process experienced by men and women on social media. This study also explores the differences in psychological impacts after love-bombing on both genders, especially among teenagers and young adults in the context of Indonesian urban culture. The method used is qualitative with a virtual ethnography approach, which allows the author to understand cultural phenomena in online spaces, especially on platforms such as WhatsApp and TikTok. Data collection techniques include participant observation, in-depth interviews, literature studies, and digital data archiving. The results of the study show that victims of love-bombing, both men and women, receive excessive attention from the perpetrators who aim to gain control over the victim or simply overcome their boredom. Love-bombing causes profound psychological impacts: men experience trauma and decreased self-esteem, while women face a long recovery process to rebuild independence. The liminality phase is characterized by changes in the perpetrator's behavior that create confusion and uncertainty, making men feel lost and women experience emotional dependence.